2006
DOI: 10.1017/s0950268806006030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Helicobacter pylori infection among healthy 3- to 5-year-old Israeli Arab children

Abstract: We determined the prevalence and risk factors of H. pylori infection among 197 healthy 3- to 5-year-old Israeli Arab children, in a population under socioeconomic and environmental transition. Data on the socioeconomic and environmental characteristics were obtained by personal interviews. The presence of H. pylori infection was identified using an ELISA kit for detection of H. pylori antigens in stool specimens. The prevalence rate of H. pylori infection was 49.7% (95% CI 42.8-56.67). It varied significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 22 publications
3
38
0
5
Order By: Relevance
“…Fifty percent of the children were H. pylori positive at this age [23]. Families of these children live in three villages in northern Israel.…”
Section: Methodsmentioning
confidence: 99%
“…Fifty percent of the children were H. pylori positive at this age [23]. Families of these children live in three villages in northern Israel.…”
Section: Methodsmentioning
confidence: 99%
“…The risk factors for H. pylori infection involve living conditions in childhood, a sensitive period of acquiring the infection [7]; and include low parental education, crowded households and large families [2, 68]. H. pylori -infected parents and siblings comprise a main reservoir of the infection, and they increase the likelihood of its acquisition in young children [4, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Low socioeconomic status (SES), low maternal education and living in crowded conditions are the main risk factors of H. pylori infection [8,12]. In addition, H. pylori ‐infected parents and siblings seem to play an important role in infection transmission [2,6,13–18], however, the duration of this effect remains unclear. Most these studies were cross‐sectional, thus a common source exposure could not be ruled out leaving the relative importance of intra‐familial transmission of H. pylori questionable.…”
mentioning
confidence: 99%
“…In a previous study, we found a prevalence of 49.7% of H. pylori infection among 3 to 5‐year‐old Israeli Arab children [14]. The risk of infection was increased in toddlers having a sibling infected with H. pylori and in those living in low SES village [14].…”
mentioning
confidence: 99%